Legal Implications and Responsibilities of Notaries for Forgery of Sale and Purchase Agreement Deeds by Notaries - Samosir, Tetti; Sihombing, B. F.; Listina, Novia (Dinasti Research, 2026)
This study examines the legal implications and liability of a Notary for the forgery of a Sale and Purchase Agreement Deed that occurred due to the Notary's negligence in carrying out his/her obligations. The research method used is normative juridical with a statutory approach and a case approach, based on the theory of legal certainty and the theory of legal responsibility. The results of the study indicate that the Notary's negligence in verifying the identity of the parties and the authenticity of the document resulted in the deed losing its authenticity based on Article 1868 of the Civil Code and can be declared null and void (nietig van rechtswege) based on Article 1320 of the Civil Code. The Notary's liability is multidimensional, including criminal liability based on Articles 263 and 264 of the Criminal Code, civil liability based on Article 1365 of the Civil Code, and administrative liability through the Notary Supervisory Board mechanism, as reflected in the Denpasar District Court Decision Number 89/PID.B/2020/PN DPS. The Notary's professionalism and thorough attitude are the main foundations in realizing legal certainty for the community.